The role of the astrocyte in subarachnoid hemorrhage and its therapeutic implications - Li, Rong; Zhao, Min; Yao, Di; Zhou, Xiangyue; Lenahan, Cameron; Wang, Ling; Ou, Yibo; He, Yue (Frontiers in Immunology, 2022)
Subarachnoid hemorrhage (SAH) is an important public health concern with high morbidity and mortality worldwide. SAH induces cell death, blood‒brain barrier (BBB) damage, brain edema and oxidative stress. As the most abundant cell type in the central nervous system, astrocytes play an essential role in brain damage and recovery following SAH. This review describes astrocyte activation and polarization after SAH. Astrocytes mediate BBB disruption, glymphatic–lymphatic system dysfunction, oxidative stress, and cell death after SAH. Furthermore, astrocytes engage in abundant crosstalk with other brain cells, such as endothelial cells, neurons, pericytes, microglia and monocytes, after SAH. In addition, astrocytes also exert protective functions in SAH. Finally, we summarize evidence regarding therapeutic approaches aimed at modulating astrocyte function following SAH, which could provide some new leads for future translational therapy to alleviate damage after SAH.